Metoda Funkcji Własnych w Zagadnieniach Termosprężystości I Elektrosprężystości - Grinczenko, W.T. (Engineering Transactions, 1972)
The aim of the paper consists in the application of the classical methods of eigenfunctions to the spatial problems of elasticity and the coupled problems of electro-elastic vibrations of piezoceramic bodies. The eigenfunction expansions have been presented in the following cases: a sphere, a layer in Cartesian and parabolic coordinates, a circular cylinder and a cone, a paraboloid on revolution, an elongated paraboloid of revolution, a wedge, and the problems concerning finite regions.